Challenges faced by nurses in managing pain in a critical care setting - Subramanian, Pathmawathi; Allcock, Nick; James, Veronica; Lathlean, Judith (Wiley, 2011)
Aim.  To explore nurses' challenges in managing pain among ill patients in critical care. Background.  Pain can lead to many adverse medical consequences and providing pain relief is central to caring for ill patients. Effective pain management is vital since studies show patients admitted to critical care units still suffer from significant levels of acute pain. The effective delivery of care in clinical areas remains a challenge for nurses involved with care which is dynamic and constantly changing in critically ill. Design.  Qualitative prospective exploratory design. Methods.  This study employed semi structured interviews with nurses, using critical incident technique. Twenty-one nurses were selected from critical care settings from a large acute teaching health care trust in the UK. A critical incident interview guide was constructed from the literature and used to elicit responses. Results.  Framework analysis showed that nurses perceived four main challenges in managing pain namely lack of clinical guidelines, lack of structured pain assessment tool, limited autonomy in decision making and the patient's condition itself. Conclusions.  Nurses' decision making and pain management can influence the quality of care given to critically ill patients. It is important to overcome the clinical problems that are faced when dealing with pain experience. Relevance to clinical practice.  There is a need for nursing education on pain management. Providing up to date and practical strategies may help to reduce nurses' challenges in managing pain among critically ill patients. Broader autonomy and effective decision making can be seen as beneficial for the nurses besides having a clearer and structured pain management guidelines.